(untitled) (Itinera, 2021)
The main aim of the article is to explain the beginning of the Roman painter Francesco Lo Savio’s career from 1957 to 1959. This part of his production has long been unknown because it was considered too distant from the mature works. During those years Lo Savio is still tied to his training in Informal Art. Moreover, the work of this period also show influences coming from American art, in particular, from the pictorial research of Mark Rothko. This essay illustrates why these works should be considered an important step, although germinal, in Lo Savio’s painting career. Just by analyzing the origins of his painting, it is possible to understand the next steps of his work. The works at the end of 1958 and early 1959 are, in fact, the start of his artistic path that will result in Space-Light paintings a few months later.